2016
DOI: 10.1016/j.neuron.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and Sequential Sampling from Memory

Abstract: Decisions take time, and as a rule more difficult decisions take more time. But this only raises the question of what consumes the time. For decisions informed by a sequence of samples of evidence, the answer is straightforward: more samples are available with more time. Indeed the speed and accuracy of such decisions are explained by the accumulation of evidence to a threshold or bound. However, the same framework seems to apply to decisions that are not obviously informed by sequences of evidence samples. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
332
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(362 citation statements)
references
References 155 publications
(193 reference statements)
28
332
2
Order By: Relevance
“…Likewise, a recent fMRI study has shown increased anterior prefrontal coupling with the hippocampus during remembering and planning upcoming trajectories to goal locations [5]. Oscillatory coupling between the posterior medial temporal lobe and rostrodorsal portions of mPFC has been observed during dynamic spatial imagery [45], and our data add further support that coupling between these regions could relate to comparison of novel choices with previous experience [38]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Likewise, a recent fMRI study has shown increased anterior prefrontal coupling with the hippocampus during remembering and planning upcoming trajectories to goal locations [5]. Oscillatory coupling between the posterior medial temporal lobe and rostrodorsal portions of mPFC has been observed during dynamic spatial imagery [45], and our data add further support that coupling between these regions could relate to comparison of novel choices with previous experience [38]. …”
Section: Discussionsupporting
confidence: 82%
“…Decisions often rely on prospection during multi-step events in order to anticipate a potential outcome, which is a process commonly linked with hippocampal-based memory ([7,3537]; see [38] for review). Furthermore, spatial planning in novel environments is usually associated with the use of a hippocampal-based internal model formed by exploration of the physical world [11], yet corresponding evidence of hippocampal involvement during on the fly planning without extensive prior learning has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…S4). In our task, the momentary evidence entering into the accumulation process can be thought of as the difference between a noisy sample from a sensory representation of motion direction held in visual short-term memory and a fixed choice criterion (22). Under this account, the reliability of the sensory representation, controlled by coherence, and the placement of the choice criterion, controlled by distance, jointly determine the signal-to-noise ratio of evidence accumulation and thereby the probability that a choice is correct.…”
Section: Behavioural Validation Of Experimental Approachmentioning
confidence: 99%
“…Research foci have included the posterior parietal cortex (Glimcher et al, 2005; Louie et al, 2013), the hippocampus (Shadlen and Shohamy, 2016), and the role of visual attention (Hare et al, 2011; Krajbich et al, 2010). While these lines of investigation remain active, a series of recent breakthroughs links good-based decisions specifically to the activity of different neuronal populations in the OFC.…”
Section: Introductionmentioning
confidence: 99%